Qatar’s defense diplomat to achieve national interests - Abdelmageed, Ali Mohammed Saeed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study shows that the use of defense diplomacy is a necessity dictated by changes in the international environment after the Cold War period, with the aim of trying to achieve the goals without engaging in confrontation with the enemies, which is the art of using force and employing it to force the enemy and forcing him to change his position on the conflict, and the State of Qatar succeeded in its siege in using its strengths and strengthening its weaknesses resulting from its geopolitical situation by properly using the means of defense diplomacy.